(untitled) (Journal of Music Research Online, 2022)
As an exterior force of relations and habits, feminism is conceived as a failure that needs a radical rethink. In this conceptualisation, feminism has failed to remove gender bias from institutions of work and in music it has failed to solve the inequalities of gender and race. Drawing on the philosophy of Deleuze as applied by Elizabeth Grosz, I explore what an immanent approach to thinking about the dynamics of feminist work and its habits in music might do to generate new understandings. I begin from the premise that the disciplinary apparatus of the modern institution makes everything the same, neutralising gender differences and eradicating any possibility for variation and unpredictability. I then shift into immanent thinking, arguing that when music performance in the higher education music institution is separated from the strictures of music curriculum and assessment regimes, transformations become possible. To illustrate this idea, I discuss a student performance of Bruno Mars’ song, Chunky, mashed with Michael Jackson’s PYT (Pretty Young Thing), at a Western Sydney University Art of Sound Concert presented in the Playhouse Theatre in October 2018. I argue that the performance, moves out of the rigidly coded gender norms of the institution into the plane of immanence.